Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbasis Pertanyaan Kritis Terhadap Hasil Belajar Siswa Materi Laju Reaksi - Elvi Sayani; Ani Sutiani (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
One of the subject matter of Chemistry in high school, loaded with concepts is Reaction Rate that be better taught through Guided Inquiry based on critical questions. This study aims to determine the learning outcomes learned through Guided Inquiry learning model based on critical questions is higher than Direct Instruction learning model. The study population was all students of class XI MIA SMA Negeri 1 Pantai Cermin which amounted to three classes adds up to 35 to 40 students. The sampling technique in this study was purposive sampling. The selected sample is XI MIA 2 as an experimental class given the treatment of the guided inquiry model based on critical questions and XI MIA 1 as a control class treated with DI model. The results showed student learning outcomes in the experimental class at 86% and in the control class at 75% while student learning activities in the experimental class at 84.6% and in the control class at 72.7%. Hypothesis test results show tcount> ttable (8.4289> 1.668), meaning that H0 is rejected and Ha is accepted, that is the results of student chemistry learning using the GI model based on critical questions higher than learning with DI model.